Efektivitas Model Problem Based Learning dalam Meningkatkan Pemahaman Nilai Akhlak pada Pembelajaran Pendidikan Agama Islam - Sumiah Nasution; Siti Istianah (Educational Journal, 2026)
This study aims to analyze the effectiveness of the Problem-Based Learning model in improving students’ understanding of moral values in Islamic Religious Education. The research employed a quantitative approach using a quasi-experimental pretest–posttest design with a sample of 30 students. The instrument used was a moral value comprehension test. Data were analyzed using descriptive statistics, normality testing, and the Wilcoxon test. The results showed that the mean score increased from 60.20 to 78.93. The Wilcoxon test produced a significance value of < 0.001, indicating a significant difference between pretest and posttest scores. These findings demonstrate that the Problem-Based Learning model effectively improves students’ understanding of moral values. This learning model encourages active participation, critical thinking, and reflective moral reasoning. Therefore, Problem-Based Learning can be used as an innovative instructional strategy to enhance the quality of Islamic Religious Education.